2010
DOI: 10.1590/s1808-86942010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Experiência de sete anos em pacientes com angiofibroma nasofaríngeo juvenil

Abstract: Juveni le nasopharyngeal angiofibroma (JNA) is a rare tumor in adolescent males. It originates in the nasopharynx. Aim: to present the experience of JNA management at an Otorhinolaryngology Service between 2001 and 2008. Materials and Methods: Demographical data, clinical presentation, investigations as well as the treatment of sixteen JNA patients were reviewed and collected from medical records from the ORL Service. Design: Cross-sectional, retrospective and descriptive study. Results: All JNA patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 31 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…In the present study most of the patients (92%) belonged to age group of 11-20 years. Almost similar data was published in by Lara et al 16 Our study showed that all the patients were male. Genetic studies have demonstrated a close relation between JNA and androgen receptor expression, suggesting that this tumor is androgen dependent.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study most of the patients (92%) belonged to age group of 11-20 years. Almost similar data was published in by Lara et al 16 Our study showed that all the patients were male. Genetic studies have demonstrated a close relation between JNA and androgen receptor expression, suggesting that this tumor is androgen dependent.…”
Section: Discussionsupporting
confidence: 89%
“…of patients No. of Patients < 10 years Age (years) Sex Follow-up Gaillard [ 40 ] R 16 1 9 M 7 yrs Kalani [ 8 ] R 22 1 9 M 1 mo Ardehali [ 5 ] R 47 1 7 M 2.5 yrs Ferreira [ 39 ] P 9 1 9 M 1 yr Handa [ 22 ] C 1 1 8 M 6 mo Baptista [ 38 ] C 1 1 8 F 6 mo Salcone [ 37 ] C 1 1 9 M 6 mo Gupta [ 23 ] CS 8 2 1: 4 2: 6 …”
Section: Resultsmentioning
confidence: 99%
“…As occurrences in young adults from 14 to 25 years have been reported in the literature, the terminology “juvenile” exclusively for JNA is deemed to be a misnomer. Females can also be rarely affected [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Erosion of the superior orbital fissure involving the third and sixth nerves may produce diplopia. And intraorbital extension may produce proptosis [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation